Penggunaan teknik relaksasi untuk menurunkan tingkat kecemasan perawat di yogyakarta selama pandemi Covid -19 - Dewi Retno Pamungkas; Anastasia Suci Sukmawati; Rizqi Wahyu Hidayati; Ratna Yunita Setiyani Subardjo; Lynette Cusack (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: As a result of the increased number of Corona Virus Disease 2019 (COVID-19) cases in Indonesia in 2021, nurses as one of the front-liners have experienced extreme workload and stress. This has caused increased numbers of mental health problems in nurses. One of the most common problems is anxiety. Objective: This study aimed to measure the effectiveness of relaxation techniques to reduce nurses’ anxiety levels during COVID-19 pandemic. Methods: This is a quantitative study, using pre- and post- test design. Nurses’ anxiety levels were measured before and after the application of relaxation techniques, namely breathing, progressive muscle relaxation and guided imagery. A training was provided for the participants, along with module and a music video to guide their practices. Results: The application of relaxation technique for approximately two weeks after an online training significantly reduced nurses’ anxiety levels. The score of anxiety levels has significantly decreased from pre- (M= 56.51, SD= 15.80) to (M= 48.30, SD= 13.70) post- training and application, t(201) = 5.82, p < .001 (two-tailed). Conclusion: It is important to provide nurses with support that they need during pandemic or any other catastrophic events, in order to maintain their safety and well-being.